Index-Based Livestock Insurance case study: Highlights - Dror, Iddo (International Livestock Research Institute, 2015)
Iddo Dror, head of capacity development at ILRI and visiting professor at the University of Geneva, Switzerland shares key highlights of the Index-Based Livestock Insurance (IBLI) Case Study and its application, with clippings from a session taught at the Graduate School of Business, University of Cape Town, South Africa.